2022
DOI: 10.1038/s41467-022-28605-0
|View full text |Cite|
|
Sign up to set email alerts
|

A cattle graph genome incorporating global breed diversity

Abstract: Despite only 8% of cattle being found in Europe, European breeds dominate current genetic resources. This adversely impacts cattle research in other important global cattle breeds, especially those from Africa for which genomic resources are particularly limited, despite their disproportionate importance to the continent’s economies. To mitigate this issue, we have generated assemblies of African breeds, which have been integrated with genomic data for 294 diverse cattle into a graph genome that incorporates g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 81 publications
2
53
0
Order By: Relevance
“…No duplications, inverted duplications and translocations passed the quality filtering. Consistent with results from previous studies 28 , most of the post-filtering insertions and deletions identified fell into the smaller classes, though 1,796 SVs (403 deletions, 1,389 insertions and 4 inversions) of over 50kb in length were identified (Figure 1).…”
Section: Variant Statisticssupporting
confidence: 89%
See 3 more Smart Citations
“…No duplications, inverted duplications and translocations passed the quality filtering. Consistent with results from previous studies 28 , most of the post-filtering insertions and deletions identified fell into the smaller classes, though 1,796 SVs (403 deletions, 1,389 insertions and 4 inversions) of over 50kb in length were identified (Figure 1).…”
Section: Variant Statisticssupporting
confidence: 89%
“…This number is comparable to what has been seen for novel sequences (i.e. insertions) using graph genome approaches, where an extra 70Mb and 116Mb of novel sequence were reported on 5 and 4 cattle reference genomes, respectively 28,29 . After merging the filtered variants from all the samples, most of the SVs were found to be private to an individual (Figure 2), consistent with what has been observed in previous studies 1 .…”
Section: Technical Validationsupporting
confidence: 82%
See 2 more Smart Citations
“…This progression is already afoot, particularly for targets that involve complex variation, such as cancer (The Computational Pan-Genomics Consortium, 2016), plant pangenomics (Bayer et al, 2020;Liu et al, 2020;Qin et al, 2021;Li et al, 2022;Bayer et al, 2022), and metagenomics (Zhong et al, 2021). Also, when studying animals like bovines (Leonard et al, 2021;Talenti et al, 2022;Bovine Pan-Genome Consortium, 2022).…”
Section: Discussionmentioning
confidence: 99%